2022
DOI: 10.2217/cer-2021-0237
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and nonrespiratory COVID-19 complications in patients with obesity: recent developments

Abstract: This narrative review summarizes recent reports to provide an updated understanding of the multiorgan effects of SARS-CoV-2 infection in obese individuals. A PubMed search of 528 primary articles was performed, with inclusion based on novelty, relevance and redundancy. Obesity confers an increased risk for hospitalization, intensive care unit admission, severe pneumonia, intubation and acute kidney injury in COVID-19 patients. Obesity is also associated with higher levels of inflammatory and thrombotic markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…However, the more accepted theory of generalized pro-inflammatory state triggered by dysregulated cytokine synthesis predominates. [28][29][30] The sheer level of inflammation garnered from SARS-CoV-2, coupled with this smoldering low-level inflammatory state triggered by the adipose tissue, may precipitate an exaggerated cytokine release syndrome resulting in higher rates of acute organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the more accepted theory of generalized pro-inflammatory state triggered by dysregulated cytokine synthesis predominates. [28][29][30] The sheer level of inflammation garnered from SARS-CoV-2, coupled with this smoldering low-level inflammatory state triggered by the adipose tissue, may precipitate an exaggerated cytokine release syndrome resulting in higher rates of acute organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies have revealed an increased susceptibility of individuals with obesity to COVID-19 infection and a higher probability of viral test positivity compared to those without [6] , [45] . Taking into consideration the fact that SARS-CoV-2 infects human lung and other tissues through binding to angiotensin-converting enzyme 2 (ACE2) receptors on the plasma membrane [46] and the increased ACE2 receptor expression in adipose tissue, individuals with obesity are believed to have an increased ACE2 receptor expression that facilitates the entry of SARS-CoV-2 into adipocytes [47] . In this way, adipose tissue not only serves as a reservoir for the virus but may also expedite its spread to surrounding organs [48] , [49] .…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients could experience malnutrition and changes in eating habits and appetite, which would have a detrimental impact on their ability to recover and rehabilitate [11,12]. Dieticians' management for obesity and other comorbidities also helps prevent severe COVID-19 complications, including acute respiratory distress syndrome (ARDS), intubation, severe pneumonia, and sepsis [13]. Thus, the role of dietitians in such nutrition-sensitive pandemic periods must not be underestimated.…”
Section: Introductionmentioning
confidence: 99%